Politics, policies and rural poverty alleviation outcomes: Evidence from Lankao County, China. (September 2022) - Deng, Qingqing; Li, Erling; Yang, Yang
Abstract: China's anti-poverty approach featuring a targeted poverty alleviation strategy has provided a model for global poverty reduction governance. This paper builds a conceptual framework that includes political contexts, policies and rural poverty alleviation outcomes, and emphasizes the response of rural households as micro subjects to the macro political and policy environment, aiming to explore the micro mechanisms of rural poverty reduction governance at the county and rural household levels. The results are as follows: ( i ) The poverty alleviation outcomes are produced by the stimulation of political and policy resources on rural households' own conditions. ( ii ) The individual differences in poverty alleviation outcome scores are obvious. The poverty alleviation collaboration mechanism, grassroots mobilization, life improvement, livelihood support, resource conditions and livelihood capacity are the leading factors affecting the poverty alleviation outcomes. ( iii ) The organic combination of political guidance, policy support and rural households' development conditions has made the poverty alleviation outcomes more remarkable. This study provides case support for the formation of an anti-poverty theory with Chinese characteristics, and serves as a reference for poverty reduction governance in developing countries. Highlights: We propose a conceptual framework that includes political contexts, policies and poverty alleviation outcomes, and emphasizes the response of rural households as micro subjects to the macro political and policy environment. The poverty alleviation outcomes are produced by the stimulation of political and policy resources on rural households' own conditions. Poverty alleviation collaboration mechanism, grassroots mobilization, life improvement, livelihood support, resource conditions and livelihood capacity are the leading factors affecting the effectiveness of poverty alleviation.